A Feasibility Study on PREMIER Bangus Processing Plant - Balanggao, Dedrick P. (College of Engineering, 2005)
The agricultural and fisheries sector is one of the entities where the Philippines has competitive advantage over other countries as it is a nation rich in agricultural and aquatic resources. In order to define its competitive niche in the world market, much effort and resources must be expanded on development projects involving segments of this sector such as the Bangus (Milkfish or Chanos Chanos) industry that is exhibiting an increase in supply and a growing demand for its deboned products in both domestic and international markets. These characteristics are indicative of a good environment for business with Bangus as raw material. As such, the proponents of this study investigated the feasibility of establishing a small-scale Bangus processing plant in Malolos, Bulacan. Bangus us an important commodity in the Philippines that is included in the typical diet of Filipinos regardless of economic status. It is cultivated all over the country with Bulacan proving to be the most productive among provinces in recent years. With today?s fast-paced life, demand for processed products including Bangus is fast increasing. Survey showed that 41% of Class A, B and C households in the 6 most populous municipalities of Bulacan, namely Malolos, Meycauayan, Baliuag, Hagonoy, Santa Maria and San Jose del Monte, are willing to buy processed bangus products and their demand is currently unsatisfied by the local markets. As such, setting up a processing plant in Malolos which would supply to the local markets of the above municipalities would take advantage of the proximity of the raw material source as well as the target market. Production of processed bangus is technically feasible since all the technology, land, labor and material inputs required to produce the products are readily available. All the equipment can be bought locally or shipped from other countries. A 323 sq. m. vacant lot near the fish port in Panasahan with good water and electricity supply is also available. All labor requirements can be obtained within Malolos itself. Materials inputs can also be acquired in the nearby Malolos Market. The total cost of these requirements is estimated to be Php 7,706,333 given the investment and operational expenditure. From the organization and management study, it was found that the right form of ownership for the processing plant, based on the business size, setup ease, owner liability, investments and transferability/survivability is a Partnership. The plant, which is a small scale business, does not require too many levels of authority and should be easy to setup as there are only a few operations as well as employees to be handled. It also requires a relatively low investment compared to larger business ventures and just as any business seek longevity in the business world. From the financial analysis, the financial statements including the income statement, cash flow statement and the balance sheet show positive and increasing trend in the company's over all sales, net income and cash flow projections all through the 5-year study period. Furthermore, the financial ratios show a steady financial position for the company. The computed values for the Net Present Value and Internal rate of return, Php 1,696,660.16 and 38.53% respectively, reveal that setting up a Bangus Processing Plan is a viable business venture. The socio-economic profitability analysis showed that the project benefits the company, the end-users, and the community through the improvement of the standard living, lowering of prices and the patronization of local materials and suppliers. In addition, the municipal and personal income taxes that result from the project will also help the local government in funding its development projects for the benefit of the community. Furthermore, the benefit-cost ratio with a computed value of 1.17 indicates that the benefits outweigh the costs. It is important to mention that the project would not cause detrimental effects to the environment as management of its waste product will be undertaken. One of its major wastes, the offal (internal organs, bones and scales) removed during evisceration and deboning can be transformed into marketable by-products such as silage which is used as a cheap fishmeal alternative that can be sold to fish pond owners in the vicinity. Waste water on the other hand will be subjected to pre-treatment system before discharge. As stated above, there is a great demand for export of processed fish products including bangus due mainly to the increasing number of Filipinos migrating and working abroad. The company would like to take advantage of this demand in the future, as soon as stability in all aspects is achieved. From the foregoing, it can be deduced that a bangus processing plant is a viable business. Due to its potential demand abroad, it also has a high potential for growth. As such, based on the market, technical, organization and management, financial and socio-economic analyses, setting up a bangus processing plant in Panasahan, Malolos Bulacan is a feasible business venture.